Open innovation em empresas de pequeno porte: um estudo em organizações do setor de TIC - Silva, Andressa Hennig (2017)
The perspectives of Brazil, in terms of Research and Development are not optimistic, since the investments are still low. Such picture of innovation scarcity is even more noticeable in companies of small- sized. Among the possible alternatives of innovation, glimpses a open innovation (OI). In Brazil, that already exist some initiatives related to the disclosure, promotion and adoption of Open Innovation, however, it is perceived that the focus of the research hovers in the look of the large companies, thus, it is understood the relevance of the study of the thematic in a doctoral thesis ,since the reality that is proposed to be studied, that is,companies small-sized, still lacks studies. Thus, this study has as a research question: how is open innovation adopted in companies of small-sized in the information and communication technology sector? Therefore, the study is characterizing itself as a qualitative approach research, of exploratory nature, and the research strategy is configured as a multiple case study. The analysis corpus covers organizations linked to the Local Productive Arrangement of the Information and Communications Technology Sector, located in the city of Santa Maria/RS, called Software Center. Among the main results, evidenced that organizations are considered young, since the average time in the market refers to six or eight years, they count, on average, with about seventeen employees in its functional framework. It was possible to identify that most managers do not have conceptual knowledge of Open Innovation, however, this does not prevent organizations from to leave to practice on openness initiatives, in reference of the reasons for the opening, stands out the fact the organizations belong to the sector of Information and Communications technology, what forecasts close relationship with the clients in the daily processes and the culture of openness, are preponderant reasons for the adoption of Open Innovation. In addition, among the main partners of Open Innovation include clients and the innovations raise from the opening processes, being Characterizing itself mainly as incremental stamp innovations. Curiously, the managers point out that being part of the Local Productive Arrangement Software Center does not influence the process of opening the company. At the end of the study, the contribution of the thesis concerns a theoretical framework proposal, which is intends to generate insights and guide managers in the adoption of open innovation in companies of small-sized.